2021
DOI: 10.1177/10497323211037636
|View full text |Cite
|
Sign up to set email alerts
|

Culture’s Place in Quality of Care in a Resource-Constrained Health System: Comparison Between Three Malawi Districts

Abstract: Public health scholars describe “culture of quality” in terms of desired values, attitudes, and practices, but this literature rarely includes explicitly stated theories of culture formation. In this article, we apply Fredrik Barth’s transactional model to demonstrate how taking a theory-centered approach can help to identify what would be necessary to foster “cultures of quality” outlined in the public health literature. We draw on data from a study of the Republic of Malawi’s Performance and Quality Improvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Similar conclusions were reached by Mahl, et al, 2015, who conducted a combined cross-sectional study in Canadian hospitals, observing how leaders, using different leadership styles, created culture in the organisation and how this was reflected in the quality of medical services. Like the authors of previous studies, ALFadhalah, &Elamir, 2021, andPatterson, et al, 2021, concluded that the transformational leadership style, due to the fact that it creates a common culture and values within the team, is able to create a favorable working environment, employee job satisfaction and more in-depth involvement in the process, which definitely positively affects the quality of medical services (Mahl, et al, 2015).…”
Section: Results Of the Literature Reviewmentioning
confidence: 78%
See 1 more Smart Citation
“…Similar conclusions were reached by Mahl, et al, 2015, who conducted a combined cross-sectional study in Canadian hospitals, observing how leaders, using different leadership styles, created culture in the organisation and how this was reflected in the quality of medical services. Like the authors of previous studies, ALFadhalah, &Elamir, 2021, andPatterson, et al, 2021, concluded that the transformational leadership style, due to the fact that it creates a common culture and values within the team, is able to create a favorable working environment, employee job satisfaction and more in-depth involvement in the process, which definitely positively affects the quality of medical services (Mahl, et al, 2015).…”
Section: Results Of the Literature Reviewmentioning
confidence: 78%
“…Due to the fact that transformational and transactional leadership styles can create a culture of a healthy work environment, which, as noted by other authors ALFadhalah, & Elamir, 2021. In turn, a healthy work environment helps to minimize stress, burnout and staff turnover, which positively affects the quality medical services (Patterson, et al, 2021).…”
Section: Results Of the Literature Reviewmentioning
confidence: 99%
“…Culture, comprised of shared norms, values, knowledge, artefacts, and practices, was found to play an important role in health workers’ efforts to improve the quality of PHC. For example, QI efforts appeared to thrive in PHC settings with strong culture of using data to orchestrate healthcare improvements, where health workers’ attitudes shift to focus more on the needs of patients (e.g., the desire to alleviate pain and reduce suffering), and where HCWs learn better and systematic approaches to solving problems [ 46 , 47 , 52 , 55 ]. Additionally, culture of quality manifested in health workers being able to work across disciplinary boundaries, where QI initiatives stir up healthy competition, and where participants reported collective responsibility for cohesion, meritocracy, a strong sense of taking responsibility for failure and success, and high standards in the PHC setting or workplace [ 55 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…QI interventions can flourish in organizations and teams with the right norms and where culture is supportive. A new way of solving intractable problems, regular team reviews that are focused on quality of care [ 52 ], finding ways to cope positively with scarcity when resources aren’t adequate and lack of control at lower levels in centralized PHC settings [ 55 ] were mentioned. A quality culture with shared values, attitudes, practices at the organization level includes regular data analysis that drives action and improvement cycles, with feedback loops built around effective communication where QI progress is shared with stakeholders who in turn are responsive.…”
Section: Resultsmentioning
confidence: 99%
“…The authors of the papersALFadhalah, & Elamir, 2021 also came to similar results (ALFadhalah & Elamir, 2021Patterson, et al, 2021). Even the authors of Liou & Dellmann-Jenkins, 2020, noticed that it is not a group culture, hierarchical power building and a breakdown in communications that cannot positively affect the quality of services provided, but is…”
mentioning
confidence: 78%